Eupalitin from Asparagus falcatus (Linn.) has anticancer activity and induces activation of caspases 3/7 in human colorectal tumor cells - Ghalib, Gaza Murad; Mehdi, Sayed Hasan; Hashim, Rokiah; Sulaiman, Othman; How, Fiona Ni Foong; Ahamed, B. M. Khadeer; Abdul Majid, Amin Malik Shah; Ahmed, Faiyaz (Academic Journals, 2013)
3,5,4′-Trihydroxy-6,7-dimethoxy-flavone (Eupalitin) has been isolated from the leaves of Asparagus falcatus (Linn.). Anti-proliferation and apoptosis studies were conducted on eupalitin. Results showed that eupalitin exhibited significant cytotoxicity against human colorectal tumor cells. It is found that eupalitin induces the activation of caspases 3/7, a hallmark of apoptosis. The study suggests that the anti-proliferative property of eupalitin towards the human colorectal tumor cells may be probably due to its capability to induce apoptosis in cells.